2021
DOI: 10.48550/arxiv.2109.11480
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improving Tuberculosis (TB) Prediction using Synthetically Generated Computed Tomography (CT) Images

Abstract: The evaluation of infectious disease processes on radiologic images is an important and challenging task in medical image analysis. Pulmonary infections can often be best imaged and evaluated through computed tomography (CT) scans, which are often not available in low-resource environments and difficult to obtain for critically ill patients. On the other hand, X-ray, a different type of imaging procedure, is inexpensive, often available at the bedside and more widely available, but offers a simpler, two dimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…CXR data may be drawn upon by multimodal deep learning models and combined with other modalities such as ECGs to better predict specific disease states [115,116]. Early work has even shown that two-dimensional CXRs can be used to reconstruct three-dimensional CT images and improve pathology detection and classification efforts [117]. Interpretation automation may benefit patients in communities lacking radiologist expertise and where investigations presently go unreported.…”
Section: Discussionmentioning
confidence: 99%
“…CXR data may be drawn upon by multimodal deep learning models and combined with other modalities such as ECGs to better predict specific disease states [115,116]. Early work has even shown that two-dimensional CXRs can be used to reconstruct three-dimensional CT images and improve pathology detection and classification efforts [117]. Interpretation automation may benefit patients in communities lacking radiologist expertise and where investigations presently go unreported.…”
Section: Discussionmentioning
confidence: 99%